Cognition of Risk Factors in the Occurrence of Type 11 Diabetes Among Rural Resident Parents in Awka Anambra-State - Ngozi, Orajekwe Veronica (Journal of Public Policy and Local Government (JPPLG), 2025)
The study was aimed at ascertaining cognition of risk factors in the occurrence of type 11 diabetes among rural parents in Awka Community of Anambra-State. In line with the objectives of the study three research questions and two null hypotheses were postulated. Related literature was reviewed and summarized. Cross sectional survey research design was adopted for the study. The sample for the study consisted 200 male and female adults were drawn by multi-stage sampling procedure. Data were gathered by means of structured interview protocol. Data obtained were analyzed using descriptive statistics of frequency and percentages as well as inferential statistics of chi-square. The findings among others showed that many adults were not cognizant of physical, social and emotional risk factors of type 11 diabetes. Gender and age were significant factors that influence cognition of risk factors to type 11 diabetes by the respondents. Based on the findings recommendations were made pertinent among which is designing intervention programme in the form of diabetes education by health educators for the rural populace in Anambra-State.